Long-term stability of conservative orthodontic treatment in a patient with temporomandibular joint disorder - Silvia Naomi Mitsui; Akihiro Yasue; Shingo Kuroda; Eiji Tanaka (Wolters Kluwer Medknow Publications, 2016)
This article reports the orthodontic treatment of a 20-year-old patient with dental crowding and temporomandibular joint disorders (TMDs). The patient presented moderate anterior crowding with a Class I molar relationship and masticatory disturbance in the mandibular position induced by previous splint therapy. Orthodontic treatment with multi-bracket appliance was initiated to correct the anterior crowding in both dental arches, after the extraction of first premolars and third molars, and also to maintain the splint-induced position of the condyles. After 26 months of treatment, an acceptable occlusion was achieved without any TMD symptoms. After 18-month retention, flattening on the right condyle was observed, possibly as an adaptative remodeling. After 16-year retention period, the occlusion was maintained without recurrence of any TMD symptoms, indicating a long-term stability of occlusion and temporomandibular joint (TMJ) components. Our results suggest the possibility of compromised treatment in patients with TMD to achieve a long-term stability in occlusion and TMJ function.